Microtus (Stenocranius) gregalis - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus (Stenocranius) gregalis (Pallas 1779) [Mus] gregalis Pallas 1779, Nova Spec. Quad. Glir. Ord.: 238. Type Locality: Russia, Siberia, E of Chulym River. Vernacular Names: Narrow-headed Vole. Synonyms: Microtus (Stenocranius) angelicus Hinton 1910; Microtus (Stenocranius) angustus Thomas 1908; Microtus (Stenocranius) brevicauda Kastschenko 1901; Microtus (Stenocranius) buturlini (Ognev 1922); Microtus (Stenocranius) castaneus Kashkarov 1923; Microtus (Stenocranius) dolguschini Afanasiev 1939; Microtus (Stenocranius) dukelskiae Ognev 1950; Microtus (Stenocranius) egorovi Baranov and Feigin 1980; Microtus (Stenocranius) eversmanni (Poljakov 1881); Microtus (Stenocranius) kossogolicus (Ognev 1923); Microtus (Stenocranius) kriogenicus Rekovets 1978; Microtus (Stenocranius) major (Ognev 1923); Microtus (Stenocranius) montosus Argyropulo 1932; Microtus (Stenocranius) nordenskioldi (Poljakov 1881); Microtus (Stenocranius) pallasii Kastschenko 1901; Microtus (Stenocranius) raddei (Poljakov 1881); Microtus (Stenocranius) ravidulus Miller 1899; Microtus (Stenocranius) sirtalaensis Yung 1966; Microtus (Stenocranius) slowzowi (Poljakov 1881); Microtus (Stenocranius) talassicus Heptner 1948; Microtus (Stenocranius) tarbagataicus Ognev 1944; Microtus (Stenocranius) tianschanicus Buchner 1889; Microtus (Stenocranius) tundrae Ognev 1944; Microtus (Stenocranius) unguiculatus (Vinogradov 1935); Microtus (Stenocranius) zachvatkini Heptner 1945. Distribution: Discontinuous distribution in four regions. Largest range is in forests or steppes from Volga River eastward through Kazakhstan, across the Pamirs, Tien Shan and Altai Mtns, NW China (NW Xinjiang), N Mongolia, and Transbaikalia to Amur area and NE China (Heilongjiang, Nei Mongol, Hebei, and Henan; Zhang et al., 1997); another area is to the north in the Lena River Basin; last two are farther north in the Siberian tundra, where one area stretches from the Kolyma River area west to Taymyr Peninsula, the other from mouth of the Ob River to the White Sea. Absent from the ...